Perkembangan Museum Kerinci (Tinjauan Historis) - Arki Aulia Hadi; Jamal Mirdad (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2021)
This paper aims to explain the history and development of the Kerinci Museum. Kerinci Museum is one of the museums on the prop. Jambi and is a state museum which is located outside the capital city of Jambi province, precisely in Kab. Kerinci. The research method in this paper uses historical research methods, namely heuristics (source collection), source criticism, synthesis (data analysis), historiography (writing). The results showed that the Kerinci Museum was built to maintain the values ​​and culture of the Kerinci community, both in the form of Cultural Heritage Objects (BCB) as well as customs and traditions. The early Kerinci Museum was founded and experienced obstacles, such as conflicts over land which still belonged to residents and the construction site. The Kerinci Museum construction process went through three stages. After being founded, this museum experienced another problem, namely the very minimal collection. Until this research was completed, the Kerinci Museum was still looking for objects suspected of being cultural heritage to be used as collections.